Déposition par Pulvé Risation Cathodique Radio Fréquence et Caracté Risation Électronique, Structurale et Optique de Couches Minces du Dioxyde de Titane - K. Hafidi; M. Azizan; Y. Ijdiyaou; E. L. Ameziane (Active and Passive Electronic Components)
Deposited titanium oxide thin films are used as optical protector films for several materials and as energy converters for solar cells. In this work, titanium oxide thin films are deposited on c-Si and glass substrates by reactive radiofrequency sputtering. All the deposits are grown at ambient temperature and the sputtering gas is a mixture of oxygen and argon with an overall pressure of 10−2 mbar. The oxygen partial pressure ratios varies from 5% to 20%.